2013
DOI: 10.1186/1472-6882-13-204
|View full text |Cite
|
Sign up to set email alerts
|

Neuritogenic effect of standardized extract of Centella asiatica ECa233 on human neuroblastoma cells

Abstract: BackgroundIn order to gain insight into neuroprotective effects of ECa 233, a standardized extract of Centella asiatica, previously demonstrated in animal models of memory impairment induced by transient global ischemia or intracerebroventricular injection of β-amyloid, the effect of ECa 233 on neurite outgrowth of human IMR-32 neuroblastoma cell line was investigated.MethodsCells were seeded and incubated with various concentrations of ECa 233. Morphometric analysis was carried out by a measurement of the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Based on the previous report of ECa 233 increased activity of ERK and Akt in human neuroblastoma (Wanakhachornkrai et al, 2013), we further investigated effects of ECa 233 on the expression of FAK, Akt, and MAPK in HaCaT. As expected, ECa 233 was found to enhance the phosphorylation of FAK, Akt, (Figure 4) and ERK, p38 MAPK ( Figure 5).…”
Section: Discussionmentioning
confidence: 57%
“…Based on the previous report of ECa 233 increased activity of ERK and Akt in human neuroblastoma (Wanakhachornkrai et al, 2013), we further investigated effects of ECa 233 on the expression of FAK, Akt, and MAPK in HaCaT. As expected, ECa 233 was found to enhance the phosphorylation of FAK, Akt, (Figure 4) and ERK, p38 MAPK ( Figure 5).…”
Section: Discussionmentioning
confidence: 57%
“…The complex regulation of spine formation and arborization potentially implicates a variety of biological pathways and processes including histone modification, transcription factors, microRNAs, kinases, hormones and cell surface receptors [37, 38]. Although details on its molecular mechanisms are limited, Centella asiatica has been shown to activate ERK1/2 and AKT in neuroblastoma cells [39, 40], two pathways that have been shown to affect dendritic morphology as well [41, 42]. Studies are ongoing in our lab to evaluate signal transduction pathways affected by CAW and the role they play in the neuroprotective effects of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effects of Centella asiatica have been well documented [20, 61-64], yet these effects have usually been attributed to the bioactive triterpenes (asiatic acid, madecassic acid, asiaticoside, madacassoside) present in the plant. We previously reported that our original extract of CAW does not contain these triterpenes [18].…”
Section: Discussionmentioning
confidence: 99%